2015
DOI: 10.1186/s13011-015-0041-2
|View full text |Cite
|
Sign up to set email alerts
|

Social identity, social networks and recovery capital in emerging adulthood: A pilot study

Abstract: BackgroundIt has been argued that recovery from substance dependence relies on a change in identity, with past research focused on ‘personal identity’. This study assessed support for a social identity model of recovery in emerging adults through examining associations between social identity, social networks, recovery capital, and quality of life.MethodsTwenty participants aged 18–21 in residential treatment for substance misuse were recruited from four specialist youth drug treatment services - three detoxif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
73
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 36 publications
5
73
1
1
Order By: Relevance
“…RCs were seen as a vehicle through which members could become engaged in positive activities to combat social isolation and to support a return to 'normality', both key aspects of the maintenance of abstinence. Members appeared more resilient and developed meaning in their lives evidencing, for example, improved relationships with family members, and better connections with society (Irving 2011;Mawson et al 2015;Wittouck et al 2013). The involvement of RC members in problem-solving and decision-making processes was also seen to help the sustainability of recovery communities.…”
Section: The Role Of Recovery Capitalmentioning
confidence: 99%
See 2 more Smart Citations
“…RCs were seen as a vehicle through which members could become engaged in positive activities to combat social isolation and to support a return to 'normality', both key aspects of the maintenance of abstinence. Members appeared more resilient and developed meaning in their lives evidencing, for example, improved relationships with family members, and better connections with society (Irving 2011;Mawson et al 2015;Wittouck et al 2013). The involvement of RC members in problem-solving and decision-making processes was also seen to help the sustainability of recovery communities.…”
Section: The Role Of Recovery Capitalmentioning
confidence: 99%
“…Strong social networks and self-esteem play an important part in enabling individuals to recognise the significant role they can play in their own recovery (Bracken et al 2012;Kelly et al 2009;Tew et al 2012). It is common for people in recovery to experience distress, face isolation, and limited social support following the loss and erosion of family relationships (Mawson et al 2015) and loss of previous drug-network friendships (2001;Laudet et al 2006). Positive social support networks are key to supporting those in recovery (Best et al 2015a, b;Litt et al 2009;Stevens et al 2010;Timpson et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only once they can define themselves as an addict can they move towards change and establish a new non-user identity. Becoming a member of a non-drug-using social network is seen as crucial to the recovery process and involves establishing social networks that support the new identity (Mawson, Best, Beckwith, Dingle & Lubman, 2015). It is most likely in this phase that their implicit identification of themselves as dependent users starts to change to non-identification with substance use.…”
Section: Self-identification In Drug-using Behaviour Versus Identificmentioning
confidence: 99%
“…In comparison, for those people who are transitioning into drug use, the more entrenched they become in patterns of drug use and in drug-using social networks, the more they may identify with the drug-using group and internalise the values and the norms of this group which are likely to be based around drug use (Biernacki, 1986, Mawson et al, 2015. Data from this research also found the number of friends that use drugs to be significantly related to drug use frequency over time.…”
Section: Self-identification In Drug-using Behaviour Versus Identificmentioning
confidence: 99%